2006
DOI: 10.1196/annals.1371.025
|View full text |Cite
|
Sign up to set email alerts
|

Diesel Exhaust and Coal Mine Dust

Abstract: Conflicting evidence on the carcinogenicity of diesel exhaust (DE) and coal mine dust in occupational settings exist. Exposure measurement in most studies is inferred on the basis of job classifications and may lead to misclassification. Confounding behavioral factors (i.e., smoking) and occupational risk factors (exposure to asbestos, arsenic, radon) need to be considered. We evaluated the epidemiological evidence and current findings of the carcinogenicity of DE and coal mine dust in occupational settings. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…We examined whether the distinction between Appalachian and non-Appalachian mining might be related to population density. We found that population density was significantly higher in Appalachian coal-mining areas (95.5 people per square mile) than in other coalmining areas (43.0 people per square mile; Satterthwaite Some research suggests that coal miners may be at elevated risk for lung cancer, although the evidence is equivocal [48]. To address the possibility that our results are due to current or former miners who live in coal-mining areas, we conducted an additional regression model limited to the heavy Appalachian coal-mining counties (N = 66).…”
Section: Resultsmentioning
confidence: 88%
“…We examined whether the distinction between Appalachian and non-Appalachian mining might be related to population density. We found that population density was significantly higher in Appalachian coal-mining areas (95.5 people per square mile) than in other coalmining areas (43.0 people per square mile; Satterthwaite Some research suggests that coal miners may be at elevated risk for lung cancer, although the evidence is equivocal [48]. To address the possibility that our results are due to current or former miners who live in coal-mining areas, we conducted an additional regression model limited to the heavy Appalachian coal-mining counties (N = 66).…”
Section: Resultsmentioning
confidence: 88%
“…Hence, the carcinogenic activity of diesel exhaust demonstrated in rats [52] and also presumed for humans based on weak but evident epidemiological findings [53] is mechanistically explainable at the molecular level. However, the effects found in rats were only small and not reproducible at low doses of diesel exhaust (< 2000 µg/m 3 ), or shorter than life-time exposures and in other species such as mice or hamsters [52].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous health effects associated with underground coal mining have been studied, including pneumoconiosis, tuberculosis, chronic obstructive pulmonary disease (COPD), and other nonmalignant diseases of the lung (Merchant et al, 1986; Kuempel et al, 1995; Isidro et al, 2004). Studies evaluating the risk of lung cancer among underground coal miners have reported conflicting results (Ames et al, 1983; Meijers et al, 1988; Morabia et al, 1992; Swanson et al, 1993; IARC Monographs on the Evaluation of the Carcinogenic Risks to Human 1997; Jockel et al, 1998; Skowronek and Zemla, 2003; Hoffmann and Jockel, 2006; Attfield and Kuempel, 2008; Miller and MacCalman, 2010).…”
Section: Introductionmentioning
confidence: 99%